Large intrinsic anomalous Hall effect in half-metallic ferromagnet Co3Sn2S2 with magnetic Weyl fermions - Qi Wang (Nature Portfolio, 2018)
The large intrinsic anomalous Hall effect (AHE) in magnetic Weyl semimetals is expected but rarely verified experimentally. Here, Wang et al. report large intrinsic AHE with linear dependence on magnetization in a half-metallic ferromagnet Co3Sn2S2 single crystal with Kagome lattice of Co atoms, arising dominantly from the Weyl fermions.